Otomasi Pembelajaran IPS di Sekolah Dasar Pelita Hati Jember - Nugroho, Prasetyo Adi; Hutama, Fajar Surya; Suhatiningsih, Suhatiningsih; Anis, Fahimatul; Nurdianasari, Nindya; Sa'i, M. (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2025)
This study aims to analyze the implementation of the Self Managed Learning (SML) approach in Social Studies (IPS) learning and to evaluate students' learning independence as a representation of learning automation. The concept of learning automation in this context goes beyond the integration of technology; it emphasizes the development of student autonomy in managing their own learning processes actively and responsibly. The research employed a classroom action research design based on Kemmis & McTaggart's spiral model, involving 20 sixth-grade students at SD Pelita Hati Jember. The findings indicate that the SML approach, supported by learning contracts, significantly improved students’ cognitive achievements and key indicators of independent learning such as initiative, responsibility, and self-evaluation. Despite challenges in time management and intrinsic motivation, this approach proved effective in shifting from conventional instructional methods toward an empowering learning model. SML-based Social Studies instruction is highly relevant for nurturing 21st-century skills and character in elementary school students.